Estudo fitoquímico e atividades biológicas de Varronia dardani e Varronia leucocephala (CORDIACEAE) - Veloso, Carlos Arthur Gouveia (2022)
Brazil is a country that presents a vast biodiversity, where we find the Caatinga region, represented by plants of the Cordiaceae family, which are employed by local communities as an alternative for the treatment of some diseases, as is the case with the species Varronia dardani and V. leucocephala, whose infusions are used for the relief of gastric pain, menstrual colic, and arthritis. Therefore, the aim of this work was to contribute to the knowledge about these species, by studying their phytochemical and biological properties. To this end, the plant material was collected in the locations of Serra Branca-PB and Maturéia-PB and submitted to extraction processes. The crude ethanolic extract of V. dardani (CEE-VD) was submitted to the determination of total phenolics and to a quantification of rosmarinic acid, considered one of the chemotaxonomic markers of the Cordiaceae family. A screening was performed with CEE-VD to evaluate its spasmolytic activity in various organs. In addition to this biological activity, the antiproliferative activity of the extracts and fractions of all species was evaluated against human melanoma cells (A2058). Using NMR techniques, the compounds isolated from the study species were identified. The screening concerning the activity in smooth muscle, showed that CEE-VD showed a non-selective activity in the different tissues and for the different agonists tested, showing highest potency in the uterus of rats. From the ethyl acetate fraction of the CEE-VD it was possible the isolation and identification of five flavonoids, being three aglycones (isosakuranetin, naringenin, and rhamnocitrin) and two glycosylated (astragalin and isoquercitrin), besides rosmarinic acid. Regarding the cytotoxic test, the isopropanolic fraction of the extract of roots from V. dardani proved to be more active, and from this fraction the compound vardanone was isolated, the first hydroanthraquinone reported in V. dardani species. This compound, was used for a chemoinformatics study, where its set of isomers was analyzed for activity in the A2058 cell line and some interactions between amino acid residues were observed, compared to the positive controls dacarbazine and vemurafenib, drugs used in current melanoma therapy. The second most active species in the cytotoxic tests was V. leucocephala, from which it was possible to isolate a saikosaponin, already isolated previously in the species. Thus, the chemical and biological results, obtained in this work, contributed to the knowledge about the genus Varronia, furthermore, the study revealed new possibilities for research on these species involving the search for new secondary metabolites, mainly of the class of quinones.